Advertising a Particularly Precarious Occupation: Nanny Ads on Craigslist. Issue 2 (4th March 2018) - Lair, Craig D.; Andrews, Christopher K.
ABSTRACT: Domestic work has long been a particularly precarious occupation in that it is subject to certain risks and vulnerabilities that make it a highly insecure, unstable, uncertain form of work that often provides very limited economic and social benefits to those who engage in it. In this article we explore whether employers are willing to advertise the particularly precarious aspects of domestic work in job advertisements for nannies. Based on a content analysis of nanny ads posted on the Craigslist pages for San Francisco, Los Angeles, New York, Seattle, and Chicago, we find that nearly half (45%) of the ads in our population contained an actual and/or potential indicator of one or more particularly precarious aspects of domestic work. While these indicators came in many specific forms, they can be grouped into two general categories: (1) ads that are actually or potentially discriminatory and (2) ads that indicate an employer may not see being a nanny as a "real" job.